Identifying Risk Factors for Left Ventricular Thrombus in Patients with Ischemic Left Ventricular Aneurysm Using Cardiac MRI - Wu, Yanfang; Wang, Hui; Wang, Zhiyan; Hua, Chang; Xiong, Ran; Fu, Hao; Lv, Qiang; Xu, Lei; Du, Xin; Dong, Jianzeng (Thrombosis and Haemostasis, 2025)
Ischemic left ventricular (LV) aneurysm is associated with LV thrombus and subsequent embolic events. However, there is currently no evidence-based recommendation for anticoagulation in these patients.To determine the characteristics of LV aneurysms associated with a high risk of thrombus formation.This retrospective study included all hospitalized patients with ischemic LV aneurysm who underwent cardiac magnetic resonance (CMR) from September 2015 to June 2023. Baseline characteristics and CMR parameters were compared between patients with and without LV thrombus. Factors associated with LV thrombus were identified using univariable and multivariable logistic regression analyses.Among the 317 patients included in this study, 88 (27.8%) had LV thrombus. Patients with LV thrombus demonstrated a higher prevalence of heart failure, lower left ventricular ejection fraction, and greater volume, mass, and global extent of late gadolinium enhancement (LGE). They also exhibited distinct LV aneurysm characteristics, such as a larger maximum transverse dimension (maximum width), a wider aneurysm neck, and a higher aneurysm shape index (ratio of maximum length to neck width). Multivariable logistic regression analyses identified aneurysm neck width (OR 1.33 per 5 mm, 95% CI 1.00–1.77, P = 0.047), shape index (OR 1.63 per 20%, 95% CI 1.23–2.16, P = 0.001), and LGE global extent of >50% (OR 6.58, 95% CI 3.04–14.27, P < 0.001) as significant predictors of LV thrombus.A wider aneurysm neck, a higher aneurysm shape index, and LGE global extent >50% are associated with LV thrombus in patients with ischemic LV aneurysm.
Keywords: ischemic heart disease; left ventricular aneurysm; ventricular thrombus; cardiac magnetic resonance